DEVELOPMENT OF MICROORGANISMS AND ISSUES OF ADAPTATION TO THE EXTERNAL ENVIRONMENT (Multidisciplinary Journal of Science and Technology, 2024)
The life of microorganisms is closely related to the conditions of the external environment. The better the conditions of the external environment, the faster the development of the organism. Microorganisms adapt to environmental conditions. This article discusses issues such as the adaptation of microorganisms to the external environment, the effects of temperature, durability, the specificity of sterilization, and the importance of radiant energy.